2021
DOI: 10.3390/horticulturae7110435
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Supplementation of Clove Fruit Extract and Salicylic Acid Maintains the Performance and Antioxidant Defense System of Solanum tuberosum L. under Deficient Irrigation Regimes

Abstract: A field trial was conducted twice (in 2020 and 2021) to evaluate the effect of clove fruit extract (CFE) and/or salicylic acid (SA), which were used as a foliar nourishment, on growth and yield traits, as well as physiological and biochemical indices utilizing potato (Solanum tuberosum L.) plants irrigated with deficient regimes in an arid environment. Three drip irrigation regimes [e.g., well watering (7400 m3 ha−1), moderate drought (6200 m3 ha−1), and severe drought (5000 m3 ha−1)] were designed for this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 126 publications
1
10
0
Order By: Relevance
“…Inoculation with R. leguminosarum and P. putida was associated with increased proline and soluble sugar contents in inoculated plants compared with those in non-inoculated plants. These osmoprotectants alleviated oxidative stress and boosted plant tolerance through diminishing ROS detoxification induced by drought stress, which conserved metabolic functions and enhanced physiological activities 38 , 39 . Furthermore, increased osmolyte accumulation reduced the cellular osmotic potential, which provided adequate water absorption from the soil, which in turn boosted cell turgor pressure, maintained the cell water status, and preserved the membranes even under severe drought stress 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation with R. leguminosarum and P. putida was associated with increased proline and soluble sugar contents in inoculated plants compared with those in non-inoculated plants. These osmoprotectants alleviated oxidative stress and boosted plant tolerance through diminishing ROS detoxification induced by drought stress, which conserved metabolic functions and enhanced physiological activities 38 , 39 . Furthermore, increased osmolyte accumulation reduced the cellular osmotic potential, which provided adequate water absorption from the soil, which in turn boosted cell turgor pressure, maintained the cell water status, and preserved the membranes even under severe drought stress 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The application of biostimulants in agriculture to increase crop yields under stressful conditions has received attention recently [24][25][26][27]. Cis-zeatin-type cytokinins (c-Z-Ck) are a type of cytokinin (CK) that has received less attention than trans-zeatin (t-Z-Ck) isomers or other highly active CKs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its diverse composition, CFE was proposed as a plant biostimulator. The enhanced mobilization of inorganic metabolites solutes like ascorbic acid (Vitamin C), K, and Ca present in CFE (Table 1) to the growing plumule and/or the increase in amylase activity and reducing sugars, contributing to early vigor and increased plant growth, may explain the improved plant growth traits (i.e., area of leaves per plant, dry weight, and shoot fresh) caused by CFE application (Afzal et al, 2012;Desoky et al, 2021b). Also, the phenolic component is critical to decline the damaging effects of drought stress in the plant (Naikoo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rady and Mohamed (2015) and Desoky et al (2020b) reported that plant extracts significantly improve plant growth and productivity. Lately, Desoky et al (2021b) have considered clove (Syzygium aromaticum) fruit extract (CFE) as one of these extracts. However, till now, scientists have not conducted any studies on using CFE as a bioactive stimulant to enhance plants' tolerance to Cd stress.…”
Section: Introductionmentioning
confidence: 99%